Determinant Factors of Purchase Intentions at Tokopedia in DKI Jakarta: An Integration of TAM and E-Servqual - Lardo, Dery Remmy; Legowo, Nilo; Sundjaja, Arta Moro (Binus Business Review, 2023)
The research analyzed the determinant factors for purchase intentions in Tokopedia. The conceptual model was developed based on integration of Technology Acceptance Model (TAM) and e-Servqual. The research defined purchase intention as dependent variable, attitude toward Tokopedia, perceived usefulness, and perceived ease of use as mediating variable, and self-efficacy, trust, and service quality as independent variable. The research design applied a quantitative approach with Structural Equation Modelling (SEM). The data collection used a survey method, and the sampling technique was purposive with Tokopedia users in DKI Jakarta. The sample size was determined by using 17-fold indicators, resulting in 380 respondents. The result shows that attitude affects purchase intention. Then, the determinant factors of attitude are service quality, perceived usefulness, and trust. Self-efficacy also affects perceived usefulness and perceived ease of use. However, self-efficacy does not significantly affect perceived ease of use. The coefficient of determinant of purchase intention, attitude toward Tokopedia, perceived ease of use, and perceived usefulness are 38,9%, 39,2%, 31,9%, and 17,9%. The managerial implication is also discussed using the Importance Performance Map Analysis (IPMA) approach. The Tokopedia management should focus on user experience, service quality, information quality, and data privacy protectionfor further application improvement. The findings contribute to the technology adoption knowledge by extending technology acceptance model with e-Servqual.